AMBIENTES DE INOVAÇÃO: DISCUTINDO O ECOSSISTEMA DO QUARTIER DE L’INNOVATION - Lain, Gabriela Cristina; Dorion, Eric Charles Henri; Prodanov, Cleber Cristiano; Olea, Pelayo Munhoz (Revista Prâksis, 2017)
Este trabalho tem como objetivo analisar as áreas de inovação e sua importância no desenvolvimento local e regional. Para tanto, o objeto principal de estudo será o Ecossistema de Inovação denominado Quartier de L’Innovation, localizado no Québec, no Canadá. Esse ambiente se constitui em um dos principais modelos de cooperação entre os atores do desenvolvimento regional, caracterizando-se como um dos melhores exemplos de práticas da tríplice hélice no Canadá. Esse estudo abre também a possibilidade da sua análise referendar boas práticas de inovação no Brasil e, especialmente, no Estado Rio Grande do Sul. Palavras-chaves: Inovação. Cooperação. Desenvolvimento regional. Tríplice hélice. ABSTRACT This work aims to analyze the innovation areas and its importance in local and regional development. Therefore, the main object of study is the Innovation Ecosystem called Quartier de L’Innovation, located in Quebec, Canada. This environment constitutes one of the main models of cooperation between the actors of regional development, characterized as one of the best examples of a triple helix practice in Canada. This study also opens up the possibility of its analysis to endorse good innovation practices in Brazil, especially in Rio Grande do Sul State. Keywords: Innovation. Cooperation. Regional development. Triple helix.